“CYTOKINE” MODEL OF PATHOGENESIS OF CHRONIC HEART FAILURE AND THE OPPORTUNITIES OF NEW THERAPEUTIC STRATEGY IN DECOMPENSATED PATIENTS - U. A. Vasuk; O. P. Dudarenko; E. N. Uschuk; E. L. Schkolnik; M. K. Serova (Рациональная фармакотерапия в кардиологии)
Neurohumoral model of pathogenesis of chronic heart failure (CHF) made it possible to develop new therapeutic approaches in patients with CHF . However , it became obvious that the ways of activation of neurohumoral systems in CHF are much more complicated. The increase in local synthesis of hormones causes the activation of inflammatory cytokines and protooncogenes, which have various negative effects. This allowed formulating immunoinflammatory conception of CHF pathogenesis, according to which the increase in interleukine-6 blood level is the marker of unfavorable prognosis for CHF , and the level of tumor necrosis factor-α (TNF-α) straightly correlates with severity of clinical condition and neurohumoral activity in CHF . The growth of TNF-α in CHF progressing as well as its reduction in successful treatment do not exclude the probability of positive effect of therapy , focused on the reduction of TNF-α concentration. The pathogenesis peculiarities of CHF including cytokine aggression demand the necessity of development of new therapy approaches with the use of cytokine system modulators.